Antibiotic Susceptibility of Cutibacterium acnes Strains Isolated from Israeli Acne Patients - Sivan Sheffer-Levi; Amit Rimon; Vanda Lerer; Tehila Shlomov; Shunit Coppenhagen-Glazer; Chani Rakov; Tamara Zeiter; Ran Nir-Paz; Ronen Hazan; Vered Molcho-Pessach (Acta Dermato-Venereologica, 2020)

(untitled)
Antibiotic-resistant Cutibacterium acnes has been reported worldwide, but data from Israeli patients with acne is currently lacking. This study evaluated the antibiotic susceptibility of C. acnes, isolated from 50 Israeli patients with acne to commonly prescribed antibiotics, using the Epsilometer test (E-test). Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) analysis, 16S rRNA sequencing and single locus sequence typing (SLST) molecular typing were used to identify and characterize C. acnes. Among 36 strains isolated, phylotype IA1 was most common. Resistance to at least one antibiotic was found in 30.6% of tested strains. Resistance rates were highest for erythromycin (25.0%), followed by doxycycline (19.4%), clindamycin (16.7%), minocycline (11.1%) and tetracycline (8.3%). Significant correlation was found between resistance to multiple antibiotics, with 5.6% of isolates resistant to all antibiotics tested. When reviewing resistances rate worldwide antibiotic resistance was found to be prevalent in Israel. Measures to limit the emergence of antibiotic-resistant strains of Cutibacterium acnes should be taken and alternative treatments should be sought.